Why the divine purpose theory fails: a conversation with Thaddeus Metz - Attoe, Aribiah D. 19XX- (International journal of philosophy and theology, 2021)
Thaddeus Metz’s new book ‘God, Soul and the Meaning of Life’ presents a brief analysis of supernaturalist views about the meaning of life – my specific concern being the Divine purpose theory. While the view locates meaning in the fulfilment of some divine mandate, I show that this theory is, at best, unattractive. In this essay, I challenge the view that a belief in God is not necessary for the Divine purpose theory to be viable. I show that if we were to agree that a belief in God is inconceivable, then a theory built on such a belief is, at best, wishful thinking. Arguing from a subjectivist perspective, I make clear the fact that any recourse to a godly mandate as what makes life meaningful inadvertently assumes an extrinsic and instrumental character, which makes such a pursuit an unattractive form of meaningfulness. Finally, I show that the God purpose theory is much too narrow as it fails to capture other paths to meaningfulness that do not involve a recourse to God, and also that any assigned purpose is unnecessary (and, therefore, unattractive), if God is all-knowing, all-powerful, etc.